2018
DOI: 10.1103/physreva.98.012504
|View full text |Cite
|
Sign up to set email alerts
|

Breit and QED effects on the 3d9D3/222D

Abstract: The multiconfiguration Dirac-Hartree-Fock theory is used to calculate the 3d 9 2 D 3/2 → 2 D 5/2 transition energy for Co-like ions with Z = 28 − 100. We investigate how electron correlation, frequency-independent and -dependent Breit interaction, as well as QED corrections vary along the sequence. The well understood frequency-independent Breit contribution has the largest contribution for all ions. Among the corrections to this, correlation decreases rapidly with Z, the frequency-dependent Breit contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 24 publications
2
25
1
Order By: Relevance
“…We compared the performance of three different quantum electrodynamic (QED) potentials [13,14] to estimate the accuracy of QED calculations, and reported improved theoretical excitation energies and transition wavelengths for W 58+ by at least one order of magnitude. The accuracy of the MCDHF-RCI calculations [11] allowed the authors to assign the unidentified line at λ = 34.779(4) Å from [9] to the M1 transition 3s 2 3p 4 1 D 2 → 3s 2 3p 4 3 P 2 of S-like W. The present study is an extension of our recent work on W 58+ [11].…”
Section: Introductionmentioning
confidence: 99%
“…We compared the performance of three different quantum electrodynamic (QED) potentials [13,14] to estimate the accuracy of QED calculations, and reported improved theoretical excitation energies and transition wavelengths for W 58+ by at least one order of magnitude. The accuracy of the MCDHF-RCI calculations [11] allowed the authors to assign the unidentified line at λ = 34.779(4) Å from [9] to the M1 transition 3s 2 3p 4 1 D 2 → 3s 2 3p 4 3 P 2 of S-like W. The present study is an extension of our recent work on W 58+ [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these examples, it is still not clear how accurate the QED contributions obtained by such approaches are. In particular, in recent papers of Li et al [41] and Si et al [42] accurate theoretical calculations have been performed for the ground-state transition energies in F-like and Co-like ions and have shown that the correlation effects are strongly reduced by so-called Layzer quenching effect [43,44]. Thus, the accurate account for the correlations becomes possible for these transitions and this allows one to test the QED corrections.…”
mentioning
confidence: 99%
“…This effect is about 1 eV (0.1-0.3%) in studied cases. However, it has been found that "variational effect" is significantly reduced when active space is expanding [50,51]. The frequency-dependent Breit term is about 2% of frequency-independent one (having opposite sign).…”
Section: Resultsmentioning
confidence: 99%